Slovenian Entrepreneurship Observatory 2003 - Rebernik, Miroslav; Močnik, Dijana; Knez Riedl, Jožica; Tominc, Polona; Širec, Karin; Rus, Matej; Krošlin, Tadej; Dajčman, Silvo (University of Maribor Press, 2004)
The monograph Slovenian Entrepreneurship Observatory 2003 consists of several research issues. In the first part, a short review of the current level of entrepreneurship is given, outlined on the basis of economic and statistical data. Understanding what is happening in Slovenian enterprises is important not only in order to pursue an appropriate economic policy but also in order to find the advantages and disadvantages of Slovenian companies in comparison with enterprises in other European countries. If Slovenia wishes to join the most developed European countries, it will have to speed up its economic growth. In the second part of a monograph, a number of topics, based on a survey of a sample of 672 enterprises are dealt with. We studied the relationship between banks and small and medium-sized enterprises (SMEs), female entrepreneurship, clustering, social responsibility of companies and the development of competences.